2018
DOI: 10.3892/or.2018.6297
|View full text |Cite|
|
Sign up to set email alerts
|

Suppression of YAP by DDP disrupts colon tumor progression

Abstract: Colon cancer is a commonly diagnosed cancer that often has a poor prognosis. Combined with the development of drug resistance to cancer treatment agents the treatment efficacy of colon cancer can be limited. Activation of the oncogene YAP has been shown to be related to colon cancer progression and is associated with poor prognosis, drug resistance and metastasis, even under treatment. Cisplatin (DDP) is a commonly used drug that can control carcinoma progression, although its mechanisms are poorly understood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
(28 reference statements)
1
9
0
Order By: Relevance
“…8 The diagram of ALKBH5 inhibits NSCLC growth and metastasis by regulating YAP expression and activity transduction, organ generation, stem cell self-renewal, and organ volume [22]. Therefore, this signaling pathway has attracted increasing interest in the scientific community [45,46]. Several key proteins in the MST/Hippo signaling pathway participate in tumor formation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…8 The diagram of ALKBH5 inhibits NSCLC growth and metastasis by regulating YAP expression and activity transduction, organ generation, stem cell self-renewal, and organ volume [22]. Therefore, this signaling pathway has attracted increasing interest in the scientific community [45,46]. Several key proteins in the MST/Hippo signaling pathway participate in tumor formation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…1i) analysis. Publicly available datasets (http://www.kmplot.com/analysis/index.php?p=service&cancer=lung, 2015 version) [23,27,28] were screened to analyze prognostic correlations between YAP expression and the survival of patients with lung cancer. Kaplan–Meier analysis indicated that elevated YAP expression inversely correlated with overall survival (OS; p = 1.1e − 0.9 according to the log-rank test for significance; n = 1926) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study demonstrated that NCTD suppressed YAP expression in NSCLC ( 26 ). Moreover, YAP activity has been reported to mediate drug resistance ( 27 , 28 ). To explore the effects of NCTD/DDP co-treatment on YAP, we used a luciferase reporter gene assay.…”
Section: Resultsmentioning
confidence: 99%